Theory and Evidence on Employer Collusion in the Franchise Sector - Alan B. Krueger; Orley Ashenfelter (Institute of Labor Economics (IZA), 2018)
In this paper we study the role of covenants in franchise contracts that restrict the recruitment and hiring of employees from other units within the same franchise chain in suppressing competition for workers. Based on an analysis of 2016 Franchise Disclosure Documents, we find that "no-poaching of workers agreements" are included in a surprising 58 percent of major franchisors' contracts, including McDonald's, Burger King, Jiffy Lube and H&R Block. The implications of these no-poaching agreements for models of oligopsony are also discussed. No-poaching agreements are more common for franchises in low-wage and high-turnover industries.
Keywords: J42; J41; J63; 330; collusion; no-poaching agreement; monopsony; oligopsony; franchise